(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
When breast cancer is suspected, smearing, palpation, examination of both mammary glands by ultrasound and mammography methods, cytological examination of the punctate obtained from the tumor, and histological examinations with sectoral resection, if necessary, are carried out. Examination is of great importance for diagnosis.